What factors influence UK medical students’ choice of foundation school? - Miah, Saiful (Adv Med Educ Pract, 2017)
BACKGROUND: We aimed to identify the factors influencing UK medical student applicants’ choice of foundation school. We also explored the factors that doctors currently approaching the end of their 2-year program believe should be considered. METHODS: A cross-sectional study was conducted during the 2013–2014 academic year. An online questionnaire was distributed to 2092 final-year medical students from nine UK medical schools and 84 foundation year-2 (FY2) doctors from eight foundation schools. Participants were asked to rank their top 3 from a list of 12 factors that could potentially influence choice of foundation school on a 5-point Likert scale. Collated categorical data from the two groups were compared using a chi-square test with Yates correction. RESULTS: Geographic location was overwhelmingly the most important factor for medical students and FY2 doctors with 97.2% and 98.8% in agreement, respectively. Social relationships played a pivotal role for medical student applicants. Clinical specialties within the rotations were of less importance to medical students, in comparison to location and social relationships. In contrast, FY2 doctors placed a significantly greater importance on the specialties undertaken in their 2-year training program, when compared to medical students (chi-square; p=0.0001). CONCLUSION: UK medical schools should make their foundation program applicants aware of the importance of choosing rotations based on specialties that will be undertaken. Individual foundation schools could provide a more favorable linked application system and greater choice and flexibility of specialties within their 2-year program, potentially making their institution more attractive to future applicants.